Transparency and reflection. Issue 7 (3rd October 2019) - Boyle, Matthew
ABSTRACT: Much recent work on self-knowledge has been inspired by the idea that the 'transparency' of questions about our own mental states to questions about the non-mental world holds the key to understanding how privileged self-knowledge is possible. I critically discuss some prominent recent accounts of such transparency, and argue for a Sartrean interpretation of the phenomenon, on which this knowledge is explained by our capacity to transform an implicit or 'non-positional' self-awareness into reflective, 'positional' self-knowledge.